SYAL BERMOTIF DENGAN INSPIRASI PINTU BLEDHEG MASJID AGUNG DEMAK DENGAN TEKNIK PRINTING - Sayida, Eva Faiza; Muthi’ah, Waridah (Anggada : Jurnal Desain dan Seni, 2021)
The scarf with a motif inspired by the Pintu Bledheg of the Great Mosque in Demak, is designed by developing the motif of the main ornament on the door, in order to create a new composition and design harmony without leaving strong elements that form the unity of the Pintu Bledheg itself. A scarf with a motif inspired by Pintu Bledheg, using 3 main ornaments, namely the Crown, Naga Salira and Bokor. In making the motif using the stilation design approach and design deformation. After the results of the development of this motif are formed, then the application of the scarf uses textile printing techniques. The uniqueness of the Pintu Bledheg at the Great Mosque of Demak is a sweetener that has aesthetic value to function as the main door. From choosing a firm color composition and the carving technique used, it adds to its uniqueness and makes its characteristics stronger. Apart from the aesthetic value, the philosophical meaning contained in this door is very good to be lived and disseminated.